Representative volume element for parallel fiber bundles: Model and size convergence. (August 2016) - Stapleton, S.E.; Appel, L.; Simon, J.-W.; Reese, S.
Abstract: The simulation of textiles often occurs at the meso scale, where the individual tows are treated as a homogeneous continuum. To properly utilize such models, fiber-scale models are required to obtain homogenized tow mechanics and consider fiber-scale mechanisms. The current study demonstrates a representative volume element (RVE) for parallel fiber bundles using the discrete element method (DEM). A method for localization, homogenization, boundary conditions, and random packing generation is presented. An RVE size convergence study was conducted for six different loading cases. An RVE existed for all loading cases, and the smallest RVE which represented a reasonable response contained 16 2 fibers. Several concerns were highlighted which need to be considered when deciding on an acceptable RVE size for the current model, including loading rate, undulations in the response due to individual fiber slippage, and specimen to specimen variation due to initial fiber positions.